A high sample rate, wireless instrumented wheel for measuring 3D pushrim kinetics of a racing wheelchair. (January 2021) - Chénier, Félix; Pelland-Leblanc, Jean-Philippe; Parrinello, Antoine; Marquis, Etienne; Rancourt, Denis
Highlights: We present a new instrumented wheelchair racing wheel. It is the first to measure 3D kinetics wirelessly at a high frequency of 2500 Hz. It was tested with a world-class athlete during max acceleration up to max speed. The total force increased with speed but not the tangential force. At higher speeds, the force was counterproductive at the beginning and end of the push. Abstract: In wheelchair racing, measuring pushrim kinetics such as propulsion forces and moments is paramount for improving performance and preventing injuries. However, there is currently no instrumented racing wheel that records 3D pushrim kinetics wirelessly and at a high sample rate, which is necessary for accurately analysing wheelchair racing biomechanics. In this work, we present an instrumented wheel that measures 3D kinetics at 2500 Hz. Bidirectional wireless communication is used to interface the wheel through a smart phone. The wheel was tested with a world-class racing athlete who propelled at maximal acceleration and maximal speed on a training roller. During acceleration, the peak total force increased continuously from 186 N to 484 N while the peak tangential force was constant at 171  N  ± 15 N. At higher speeds, a counterproductive tangential force was measured during the first 15% and the last 25% of the push phase, peaking at -78 N. This wheel may be of great value for both coaches and athletes to help with planning and validating training programs and adaptations to the wheelchair such as positioning. This wheel also has very high potential for further research on wheelchair racing biomechanics and on preventing shoulder pathologies associated with this sport. Graphical abstract: Image, graphical abstract